2004
DOI: 10.1200/jco.2004.08.158
|View full text |Cite
|
Sign up to set email alerts
|

Bronchioloalveolar Pathologic Subtype and Smoking History Predict Sensitivity to Gefitinib in Advanced Non–Small-Cell Lung Cancer

Abstract: Our data suggest that individuals in whom gefitinib is efficacious are more likely to have adenocarcinomas of the bronchioloalveolar subtype and to be never smokers. These observations may provide clues to mechanisms determining sensitivity to this agent and suggest that NSCLC has a different biology in patients who never smoked and those with bronchioloalveolar carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
204
2
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 677 publications
(224 citation statements)
references
References 22 publications
11
204
2
7
Order By: Relevance
“…Of these prognostic factors, only PS and lactic dehydrogenase played a significant prognostic role for OS in our study. Smoking history has been a well-known prognostic marker for survival in many clinical trials [9,10,14,15]. However, in our study, smoking history was not significantly associated with both PFS and OS.…”
Section: Discussioncontrasting
confidence: 55%
“…Of these prognostic factors, only PS and lactic dehydrogenase played a significant prognostic role for OS in our study. Smoking history has been a well-known prognostic marker for survival in many clinical trials [9,10,14,15]. However, in our study, smoking history was not significantly associated with both PFS and OS.…”
Section: Discussioncontrasting
confidence: 55%
“…Analyses of both preclinical xenograft models (14) and specimens from gefitinib-sensitive and -refractory tumors (15) did not reveal any obvious relationship between EGFR expression levels and tumor sensitivity. Retrospective epidemiologic analyses suggested that gefitinib is more likely to be effective in Japanese patients (11), individuals with adenocarcinomas of the bronchioloalveolar carcinoma (BAC) subtype, and ''never smokers'' (16).…”
mentioning
confidence: 99%
“…Gefitinib was associated with an objective tumor response rate of 10%-19% in a subset of patients, thus starting the era of personalized medicine in NSCLC. The initial clinical trial with gefitinib and other agents of its class noted that its highest efficacy was in certain subsets of mainly Asian, female, and never-smokers with adenocarcinoma histology (5,6). Understanding the biology behind these differential responses led to the discovery of the two sensitizing EGFR mutations (exon Molecular targeted therapy heralded a new era for the treatment of patients with oncogene-driven advanced-stage non-small-cell lung cancer (NSCLC).…”
Section: Era Of Targeted Therapy For Nsclcmentioning
confidence: 99%